Multiple Pickering emulsions stabilized by the same particles with different extent of hydrophobization in situ - Zhu, Yue; Chen, Tingting; Cui, Zhenggang (Frontiers in Chemistry, 2022)
Multiple emulsions are widely used in pharmaceuticals, foods and cosmetics. However, those stabilized by surfactants with different HLB values are generally unstable due to the diffusion of the surfactants between inner and outer interfaces. Here we report that multiple W/O/W emulsions can be prepared by using same particles in combination with surfactant of different concentration. The less surface-active raw CaCO3 nanoparticles can be hydrophobized to surface-active in situ by adsorption of anionic surfactant SDS, and the wettability of the particles can be controlled to suitable for stabilizing both O/W and W/O emulsions, respectively, by adjusting the surfactant concentration. With toluene as oil phase, the particles at 1.0 wt.% tend to stabilize a W/O emulsion in the presence of 3mM SDS in aqueous solution, which can then be further dispersed in an aqueous phase with 1.0 wt.% CaCO3 and SDS below 1 mM to form a W/O/W multiple emulsion. The effect of the ratio of W/O emulsion to outer water phase and the preparing methods on stabilization of the multiple emulsions were examined. With the ratio being smaller than 3:1 and by gentle magnetic stirring, the multiple emulsions stabilized by CaCO3 nanoparticles can keep stable for a period of time avoiding coalesce. This simple method not only ensures stabilization of the multiple emulsions but also avoids complicated synthesis of colloid particles with different wettability.